GLOBALISATION AND ITS IMPACT ON LABOUR RELATIONS IN ZIMBABWE - Fore, Cleopas; I. Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2021)
Globalisation created some form of standardised global labour market epitomised by flexible labour legislation and friendly employment policies and these developments have affected labour relations globally. USAID (2014) notes that Zimbabwe needed to embrace globalisation as a solution to its troubled economic and labour market challenges advising that globalisation is unavoidable, and resisting it through unfriendly labour laws and internal policieswould only lead to firms moving their business to other countries with better policies.The Zimbabwean labour relations environment is characterised by liberalised employment laws that provides for employee democracy, industry and workplace level labour relations councils namely national employment councils and works councils respectively. Inspite this, both employers and emplyees are unhappy with the current labour relations environment. The objective of this article is to understand the impact of globalisation on labour relations in Zimbabwe. It therefore adopted a qualitative research paradigm. A purposive sample of fourteen participants took part in the study wherein twelve participated in interviews and two wrote memoirs detailing their experiences. Findings showed that globalisation has impact on labour legislation. The nature of Zimbabwe’s labour relations showed two composites namely of employee participation and inherent antagonism between emloyers and employees. The article recommended that to ameliorate the negative impact of globalisation on labour relations in Zimbabwe, employees and their employers require to work together in establishing a desired labour relations culture. An integrated labour relations theoretical framework is proposed as a holistic model that can help employers and employees to understand globalisation and labour relations in its totality from internal and external factors of national and global magnitude. If globalisation is understood from its broad perspective, it will be easy to deal with the challenges it occasion.